(3GdCeO GdCbUi aj GdCSeGA GdMSfis - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s
(3ChdgG (B:s
(3GdMeO ddg bHd cd TF hYdi cd MGd Gd eWdH GdChd ai PcQ CSeGA Gddg JYGdi Ydi GdLedI hGdJaUjd hPcQ ehGQOgG hGNJdGa GdQhGjGJ ajgG hajg NeSI aUhd GdaUd GdChd ai PcQ GdGMGOjK s
(3BNQgG (B:s
(3aCeG fMf ade fYJeO efg MQakG ZdG HYO Cf QGSdg dcf dG jCef GdhdO hdGjVef GdYUeI hGddg CYde s
(3GdejcQhajde Hg Jda HSjWs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B242s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs